2011
DOI: 10.1097/hjh.0b013e3283450770
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 overexpression restores diastolic function in eNOS knockout mice

Abstract: eNOS(-/-) mice developed diastolic dysfunction; this was rescued by ET-1 transgenic overexpression. This study furthermore suggests that cardiac ET-1 overexpression in case of eNOS deficiency causes specifically the regulation of proteins playing a role in oxidative stress, myocytes contractility, and energy metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…Heart catheter examination of these mice revealed no major differences between WT mice and ET-1+/+ mice with the exception of a significantly decreased time of left ventricular relaxation constant (tau) in ET-1+/+ mice. Myocyte size and cardiac collagen content were similar in WT and ET-1+/+ mice [17]. However, under conditions of a 10-fold increase of cardiomyocyte-derived ET-1 production, observed in a mouse model of cardiomyocyte-specific ET-1 overexpression, the cardiac phenotype was characterized by an increased expression of inflammatory cytokines and an inflammatory cardiomyopathy leading to heart failure and death [41].…”
Section: Kidney Weight and Protein Excretionmentioning
confidence: 94%
See 3 more Smart Citations
“…Heart catheter examination of these mice revealed no major differences between WT mice and ET-1+/+ mice with the exception of a significantly decreased time of left ventricular relaxation constant (tau) in ET-1+/+ mice. Myocyte size and cardiac collagen content were similar in WT and ET-1+/+ mice [17]. However, under conditions of a 10-fold increase of cardiomyocyte-derived ET-1 production, observed in a mouse model of cardiomyocyte-specific ET-1 overexpression, the cardiac phenotype was characterized by an increased expression of inflammatory cytokines and an inflammatory cardiomyopathy leading to heart failure and death [41].…”
Section: Kidney Weight and Protein Excretionmentioning
confidence: 94%
“…This is remarkable, since blood pressure is clearly lower in ET-1+/+ mice in this age group indicating that there are obviously ET-1 mediated bloodpressure independent mechanisms increasing the heart weight. Vignon-Zellweger et al [17] demonstrated a two-fold elevated cardiac ET-1 mRNA expression in ET-1+/+ mice compared to the WT counterparts. Brain natriuretic peptide concentrations were slightly but not significantly higher in ET-1+/+ mice.…”
Section: Kidney Weight and Protein Excretionmentioning
confidence: 98%
See 2 more Smart Citations
“…Endothelin-1 (ET-1) has been shown to play a key role in the pathogenesis of cardiac and renal diseases [1][2][3][4][5]. It is elevated in patients with essential hypertension [6] and in particular pregnant women with pregnancy induced hypertension [7].…”
Section: Introductionmentioning
confidence: 99%